Optimising the operation of hydronic heating systems in existing buildings for connection to low temperature district heating networks - Tunzi, Michele (2016)
This thesis presents a new method developed to adapt existing hydronic systems in buildings to take advantage of low temperature district heating (LTDH). The work carried out was performed by extensive use of buildings’ energy modelling, validated through recorded data. Two different case studies were investigated and the dynamic heat demand profiles, simulated for each building, were used to evaluate plate radiators connected to single and double string heating loops. The method considered an optimisation procedure, based on supply and return temperatures, to obtain the required logarithmic mean temperature difference (LMTD). The results of the analysis are presented as the average reduction of LMTD over the heating season compared to the base case design conditions. The developed strategy was applied to a Danish single family house from the 1930s. Firstly it was hypothesised a heating system based on double string loop. Two scenarios were investigated based on the assumption of a likely cost reduction in the end users energy bills of 1% per each 1◦C reduction of return and average supply and return temperatures. The results showed possible discounts of 14% and 16% respectively, due to more efficient operation of the radiators. For the case of single loop system, the investigated scenario assumed a cost reduction in the end users energy bill of 1% per each 1◦C lower reduction of average supply and return temperature. Although low return temperatures could not be achieved, the implementation of the method illustrates how to efficiently operate these systems and for the given scenario a possible discount of 5% was quantified. The method was also applied to a UK small scale district heating (DH) network. The analysis began by assessing the buildings of the Estate having double string plate radiator systems. Assuming a likely cost reduction in the end users energy bills of 1% per each 1◦C reduction of return temperature, the optimisation led to obtain a possible discount in the end users energy bills of 14% with a possible yearly average return temperature of 41◦C, compared to the present 55◦C. Moreover, few improvements in the operation of the heat network were proposed. It was assumed to operate the buildings with underfloor heating systems (UFH) with average supply and return temperatures of 40/30◦C, whereas the ones with plate radiators with the optimised temperatures of 81/41◦C. The results shown that an overall average return temperature of 35.6◦C can be achieved operating the heat network as suggested. This corresponds to a decrease in the average return temperature of 18.6◦C compared to the present condition and to a reduction of 10% in the distribution heat losses. Finally, the lower average return temperature achievable would guarantee a better condensation of the flue gases, improving the overall efficiency of the biomass boiler. This was quantified as a possible reduction of fuel consumption of 9% compared to present conditions.